2007
DOI: 10.1089/ten.2006.0167
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulating Development: A Template for Periodontal Tissue Engineering

Abstract: The induction of bone formation by the soluble osteogenic molecular signals of the transforming growth factor-beta (TGF-beta) superfamily is a critical issue to periodontologists, molecular biologists, and tissue engineers alike, because preclinical studies in primates and clinical trials have demonstrated the bone induction capacity of bone morphogenetic and osteogenic proteins (BMPs/OPs) in clinical context. BMPs/OPs, pleiotropic members of the TGF-beta superfamily, induce de novo endochondral bone formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 85 publications
0
58
0
Order By: Relevance
“…These changes are intriguing, especially because Wnt and TGFβ signaling have both been implicated in cementogenesis [8084]. However, like the changes in PP i -associated genes, these were not identified until 26 dpn, after the primary cementum defect in Bsp −/− had been evident for some time.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are intriguing, especially because Wnt and TGFβ signaling have both been implicated in cementogenesis [8084]. However, like the changes in PP i -associated genes, these were not identified until 26 dpn, after the primary cementum defect in Bsp −/− had been evident for some time.…”
Section: Discussionmentioning
confidence: 99%
“…Taba et al [22] have showed that BMP-2 and -7 stimulate cementogenesis during periodontium development. The incisive work of Ripamonti has shown that BMPs are the soluble signals that initiate regeneration of the periodontal tissues, including the induction of cementogenesis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Or how the soluble molecular signals of the transforming growth factor-␤ (TGF-␤) supergene family are deployed so as to initiate de novo bone formation by induction [1][2][3]? Somehow more simply but very confusing in a scenario of redundancy of multiple soluble molecular signals initiating bone differentiation by induction in the primate, which are the molecular signals that initiate de novo bone formation by induction [1][2][3][4][5][6][7][8][9][10]?…”
Section: Introduction: the Induction Of Bone Formation The Emergencementioning
confidence: 99%
“…To be truthful, we have always assigned a prominent and pivotal role to the osteogenic proteins (OPs) of the TGF-␤ supergene family [4,5]. There is no bone formation by induction without the osteogenic soluble molecular signals of the TGF-␤ supergene family [1][2][3][4][5][6][7][8][9][10]. We have, however, always assigned additional prominent critical roles to biomimetic matrices capable of delivering the biological activity of the osteogenic soluble molecular signals [1][2][3][4][5][6][7][8][9][10].…”
Section: Introduction: the Induction Of Bone Formation The Emergencementioning
confidence: 99%